Optimalisasi Prospek Investasi dan Trading pada Saham PT Bank Rakyat Indonesia Tbk (BBRI) - FITRI LUTHFIA WACHDAH; Nugroho Febrianto; Angga Dwi Permadi; Gilang Ramadani; I Made Suparta (Nirta Learning Centre, 2025)
This study aims to analyze the investment and trading prospects of PT Bank Rakyat Indonesia Tbk (BBRI) shares with a fundamental and technical analysis approach. BBRI is one of the largest banks in Indonesia that focuses on financing Micro, Small, and Medium Enterprises (MSMEs), and has an important role in national economic growth. The results of fundamental analysis show strong financial performance with consistent net income, stable financial ratios, and significant credit growth through the distribution of People's Business Credit (KUR). On the other hand, technical analysis indicates a bullish trend in BBRI stock, with buy signals emerging from indicators such as Moving Average and Relative Strength Index (RSI). The combination of these two analyses provides a comprehensive guide for long-term investors and short-term traders to maximize profits while being mindful of market risks. This study concludes that BBRI stock offers an attractive investment opportunity, although it is necessary to consider external factors that may affect price movements.